A Theory of Holdouts in Wage Bargaining - Gu, Wulong; Kuhn, Peter (American Economic Review, 1998)
Holdouts (the continuation of negotiations beyond the contract expiry date) are the most common form of disputes in labor contract negotiations. We model holdouts as a delaying tactic employed by unions to obtain information about other bargaining outcomes in their industry. Novel implications of our model include a positive association between holdout duration and the number of bargaining pairs negotiating contracts simultaneously; bunching of holdout durations within these "negotiating groups"; and fewer strikes among holdouts which end later in groups. Using a large panel of contract negotiations in Canadian manufacturing, we find considerable support for these predictions.